Versatility of buccinator flaps for the treatment of palatal defects: a series of cases. Issue 4 (May 2017) - Gavin Clavero, M.A.; Simón Sanz, M.V.; Jariod Ferrer, Ú.M.; Mur Til, A.
Abstract: The buccinator flap is currently one of the best techniques for the reconstruction of defects in the oral cavity and other sites. Reconstruction of the palate is a major challenge because of the functional consequences of the excision of lesions in this area. The main goal is to maintain separation between the mouth and the nose. We have done a cross-sectional retrospective descriptive study of a series of cases reconstruction of palatal defects with buccinator flap at the University Hospital Miguel Servet in Zaragoza during a six-year period and compared our results, morbidity, and mortality with those of published series. The main complication was partial loss of the flap. We have analysed the reasons for this and report the steps needed to avoid it.